Sedimentary processes at the mouth of a tidally‐influenced delta: New insights from submarine observatory measurements, Fraser Delta, Canada. Issue 6 (7th June 2021) - Hill, Philip R.; Lintern, D. Gwyn
Abstract: This paper examines particle settling dynamics in a tidally‐influenced delta, including observations of convective settling, strongly modulated by seasonal discharge and tidal cycles. Long time series of Acoustic Doppler Current Profiler backscatter, a proxy for suspended sediment concentration in the water column, current and sediment accumulation measurements from the slope of the Fraser River delta show variability of sedimentary processes over timescales from semi‐diurnal to annual. Acoustic Doppler Current Profiler backscatter shows a lagged response to river discharge and strong diurnal/semi‐diurnal variability. Most of the tidal cycle is characterized by a buoyant effluent plume. During the ebbing phase of diurnal major tides, discrete settling events are observed extending through the entire water column. The pulse‐like nature of these events is the result of downward plunging fingers characteristic of convective settling, similar to those observed in laboratory flume experiments, and appear to be initiated at the interface between the surface buoyant plume and the underlying ambient water. Currents show strong variability in a three‐layer water column. The surface plume shows offshore and southward directed transport of sediments. The remaining water column is influenced by tidal flows, but near surface and intermediate water‐depth currents are out of phase by several hours, indicating a stratification of the basin water and decoupled propagation of surface and internal tides. This phase lag is unlikely to cause discernible facies changes, but may have implications for basin‐fill patterns in restricted basins with strong tidal range. The results of this work will help to better understand river mouth sedimentation processes and dispersal patterns in other modern deltas and in the geological record.